NEW ARTIFICIAL GRANULAR MATERIALS FOR ANALOGUE LABORATORY EXPERIMENTS: ALUMINIUM AND SILICEOUS MICROSPHERES - Rossi D.; Storti F. (My University, 2003)
Laboratory tests have been carried out to determine the physical properties of high sphericity and low density, fine grained dry granular materials. In particular, we tested hollow aluminium microspheres and hollow siliceous microspheres. Shear tests have been carried out with a Casagrande apparatus for different values of normal stress (from 12.27 to 491.8kPa) in order to determine the frictional properties of the microspheres. Diagrams of the shear stress against displacement have been used to describe the strength of the investigated materials at different confining pressures. The shear tests show that hollow aluminium and siliceous microspheres successfully replicate the mechanical behaviour of weaker layers within natural sedimentary successions undergoing deformation. The use of these artificial granular materials in specifically designed experiments indicated that they can be successfully used for constructing more ''natural'' multilayers in the laboratory.
Keywords: ANALOGUE MODELLING; ARTIFICIAL GRANULAR MATERIAL; COEFFICIENT OF INTERNAL FRICTION; COHESION; MECHANICAL STRATIGRAPHY